Integration of Shame Resilience Theory and the Discrimination Model in Supervision - William B. Lane Jr. (Teaching and Supervision in Counseling, 2020)
Shame is a destructive feeling if unaddressed leads to difficulty in the supervisory hour. A supervisorial model to address shame within supervision could guide supervisors on how to work with and diffuse the symptoms and defense mechanisms of shame. Shame Resilience Theory (SRT) and the Discrimination Model (DM) of supervision have been synthesized within this conceptual article to create the Shame Resilience Discrimination Model (SRDM) which is designed to help supervisees work through shame. Examples of how to use the model and a case example have been provided. The SRDM has been displayed in a table at the end of the article.
Keywords: shame; supervision; SRDM